2004
DOI: 10.1007/s00425-004-1215-8
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation by protein kinase CKII modulates the DNA-binding activity of a chloroplast nucleoid-associated protein

Abstract: Plastid DNA, like bacterial and mitochondrial DNA, is organized into protein-DNA complexes called nucleoids. Plastid nucleoids are believed to be associated with the inner envelope in developing plastids and the thylakoid membranes in mature chloroplasts, but the mechanism for this localization is unknown. MFP1 is a DNA-binding, coiled-coil protein associated with the thylakoid membranes of mature chloroplasts. It is also a component of nucleoids, suggesting a function at the interface of the chloroplast genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The chloroplast-targeting CK2 α-subunit is known to be present in other plant species in addition to Arabidopsis , named either plastid transcription kinase (PTK) or cpCK2 (Baginsky et al , 1999; Ogrzewalla et al , 2002; Jeong et al , 2004). PTK/cpCK2 is located in the stroma of chloroplasts and is the major kinase for phosphorylation activity in the stroma (Bayer et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chloroplast-targeting CK2 α-subunit is known to be present in other plant species in addition to Arabidopsis , named either plastid transcription kinase (PTK) or cpCK2 (Baginsky et al , 1999; Ogrzewalla et al , 2002; Jeong et al , 2004). PTK/cpCK2 is located in the stroma of chloroplasts and is the major kinase for phosphorylation activity in the stroma (Bayer et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
“…PTK/cpCK2 is located in the stroma of chloroplasts and is the major kinase for phosphorylation activity in the stroma (Bayer et al , 2012). However, only a few PTK/cpCK2 substrates have been verified experimentally to date, which include sigma factors (SIG1 and SIG6), components of the plastid-encoded RNA polymerase complex (Ogrzewalla et al , 2002; Schweer et al , 2010 b ; Türkeri et al , 2012), RNA-binding proteins (Liere and Link, 1997; Reiland et al , 2009), chloroplast nucleoid-associated protein (MFP1) (Jeong et al , 2004) and the β-subunit of the chloroplast ATPase complex (Kanekatsu et al , 1998). Large-scale phosphoproteome profiling in Arabidopsis has shown that potential CK2 phosphorylation sites are over-represented among 174 phosphoproteins in the chloroplast (Reiland et al , 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Recombinant NAD-GAPDH from wheat ( Tae NAD-GAPDH) was expressed and purified as described Piattoni et al (2013). We assayed its capacity to be phosphorylated by incubating it with extracts from mature wheat seeds or leaves in the presence of [32P]ATP and under conditions previously determined to promote activity of different plant protein kinases (Roe et al, 1997; Ikeda et al, 1999; Jonak et al, 2000; Gong et al, 2002; Jeong et al, 2004; Lalle et al, 2005; Zhang et al, 2005). As illustrated by Figure 1 (gray columns), NAD-GAPDH was phosphorylated by the seed extract in more than one condition, with the highest signal observed for that promoting WPK4 activity.…”
Section: Resultsmentioning
confidence: 99%
“…Mitogen-activated protein kinase (MAPK): 25 mM Tris-MES, pH 7.5, 12 mM MgCl 2 , 2 mM EGTA, 1 mM DTT, and 25 mM ATP at 30°C (Lalle et al, 2005). V. Casein kinase II (CKII): 10 mM Tris-HCl, pH 7.4, 50 mM KCl, 10 mM MgCl 2 , and 100 mM ATP at 30°C (Jeong et al, 2004). .…”
Section: Methodsmentioning
confidence: 99%
“…For MFP, SiR and SWIB-4 it was shown that the binding to DNA is regulated by phosphorylation. The three proteins seem not to bind to DNA when they are phosphorylated (Chi-Ham et al, 2002; Jeong et al, 2004; Melonek et al, 2012). Several kinases were found to be associated with nucleoids, e.g., the fructo-kinase like protein FLN1/2, the casein kinase CK-II, as well as two atypical ABCK1 type kinases (Lundquist et al, 2012).…”
Section: Mechanisms Underlying the Restructuring Of Plastid Nucleoidsmentioning
confidence: 99%